JANUARY EFFECT DAN SIZE EFFECT DI SEKTOR PERBANKAN YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) TAHUN 2012-2016 - Lukmanul Hakim (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
An efficient capital market hypothesis says that efficient markets react quickly to relevant information. In an efficient market, the market will quickly react to new incoming information so that it will quickly reach a new equilibrium price. In practice in the capital market appears a phenomenon that shows irregularities that contradict the concept of an efficient capital market (market anomaly). The anomalies are another January Effect and Size Effect. The purpose of this study is to examine whether (1) there is a January Effect phenomenon in banking sector companies listed in Indonesia Stock Exchange (BEI) in 2012-2016. To examine whether (2) Size affects the Return of shares in the Banking Sector listed in Indonesia Stock Exchange (IDX) 2012-2016. This study uses descriptive approach Population used in this study is the stock of banking companies listed in (BEI) While the sample is the stock of banking companies amounted to 20 companies listed in the (BEI) 2012-2016. The research method used is documentation method data, while data analysis technique using normality test, different test (T-Test). Based on the calculation of stock return value shows that before january, when janauari and after january no significant effect in banking companies. The results showed that different results were obtained in the january test after January, which obtained significant results.